Clinical Characteristics, Complications, and Reasons for Readmission following Lingual Tonsillectomy. (19th February 2019) - Merna, Catherine; Lin, Harrison W.; Bhattacharyya, Neil
Abstract : This brief communication regards the indications and complications for and rates of readmission following lingual tonsillectomy. The National Readmissions Database (NRD) 2013‐2014 was queried for all cases of lingual tonsillectomy occurring from 2013 to 2014. Among 602 lingual tonsillectomies (mean age 36.5 years, 58.2% male), the common indications for surgery were obstructive sleep apnea (58.7%), lingual tonsil hypertrophy/infection (18.8%), and neoplasia (15.9%). Overall, 49 (8.2%) of the cases were readmitted (95% confidence interval, 4.8%‐13.5%), with an average readmission duration of 3.0 days and average readmission cost of $25.4K. The most common diagnoses at readmission were bleeding (1.9% of all lingual tonsillectomy cases); dysphagia (1.7%); fever, nausea, vomiting, or diarrhea (1.6%); acute pain (1.6%); and airway obstruction (1.4%). There were no mortalities during primary or subsequent admissions. Lingual tonsillectomy across age groups is relatively free of adverse events, with overall readmission and complication rates similar to those of palatine tonsillectomy.